The resistance training dose response: meta-regressions exploring the effects of weekly volume and frequency on muscle hypertrophy and strength gains - Pelland, J. C.; Remmert, J. F.; Robinson, Z. P.; Hinson, S. R.; Zourdos, M. C. (Sports Medicine, 2026)
Background: Weekly set volume and frequency are used to manipulate resistance training dosage. Previous research has identified higher weekly set volume as enhancing muscle hypertrophy and strength gains, but the nature of the dose-response relationship still needs to be investigated. Mixed evidence exists regarding the effects of higher weekly frequency. Objective: We aimed to explore the dose-response relationships between key resistance training dosage variables (weekly set volume and frequency) and strength and hypertrophy. Methods: Before meta-analyzing the volume and frequency research, all contributing resistance training sets were classified as direct or indirect, depending on their specificity to the hypertrophy/strength measurement. Then, weekly set volume/frequency for indirect sets was quantified as 1 for `total,` 0.5 for `fractional,` and 0 for `direct.` A series of multi-level meta-regressions were performed for muscle hypertrophy and strength, utilizing 67 total studies of 2058 participants (79.1% male, 20.9% female; average age 25.16 ± 5.22 years). All models were adjusted for the duration of the intervention and training status. Results: The relative evidence for the `fractional` quantification method was strongest; therefore, this quantification method was used for the primary meta-regression models. The posterior probability of the marginal slope exceeding zero for the effect of volume on both hypertrophy and strength was 100%, indicating that gains in muscle size and strength increase as volume increases. However, both best-fit models suggest diminishing returns, with the diminishing returns for strength being considerably more pronounced. The posterior probability of the marginal slope exceeding zero for frequency`s effect on hypertrophy was less than 100%, indicating compatibility with negligible effects. In contrast, the posterior probability for strength was 100%, suggesting strength gains increase with increasing frequency, albeit with diminishing returns. Conclusions: Distinguishing between direct and indirect sets appears essential for predicting adaptations to a given resistance training protocol, such as using the `fractional` quantification method. This method`s dose-response models revealed that volume and frequency have unique dose-response relationships with each hypertrophy and strength gains. The dose-response relationship between volume and hypertrophy appears to differ from that with strength, with the latter exhibiting more pronounced diminishing returns. The dose-response relationship between frequency and hypertrophy appears to differ from that with strength, as only the latter exhibits consistently identifiable effects.